EFEKTIVITAS METODE PROBLEM POSING DALAM MENINGKATKAN KREATIVITAS - Esty Faatinisa (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
Creativity is an essential element necessary in education. When teacher or lecture create a responsive classroom environment students are less apprehensive about their creative expression and sharing those idea in class. A responsive classroom environment is optimized when teachers or lectures are respectful of unusual questions, unusual imaginations and un usual ideas. Teachers or lectures can create a supportive environment for creativity by encouraging students to see creativity as learned process. A problem posing method, encourages students to ask questions, explore a range of answers and to solve problem in many way.